Four Species Linked by Three Hybrid Zones: Two Instances of Repeated Hybridization in One Species Group (Genus Liolaemus) - Grummer, Jared A.; Avila, Luciano J.; Morando, Mariana M.; Leaché, Adam D. (Frontiers in Ecology and Evolution, 2021)
Hybridization is an evolutionary process that can generate diverse outcomes, such as reinforcing species boundaries, generating new species, or facilitating the introgression of locally-adapted alleles into new genomic backgrounds. Liolaemus is a highly diverse clade of South American lizards with ~260 species and as many as ten new species are described each year. Previous Liolaemus studies have detected gene flow and introgression among species using phylogenetic network methods and/or through comparisons of nuclear and mitochondrial DNA patterns, yet no study has systematically studied hybrid zones between Liolaemus species. Here, we compared three hybrid zones between four species in the Liolaemus fitzingerii group of lizards in Central Argentina where two species, L. melanops and L. xanthoviridis, each hybridize with two other species (L. shehuen and L. fitzingerii). We sampled three transects that were each approximately 120km in length and sequenced both mitochondrial and genome-wide SNP data for 267 individuals. In our analyses of nuclear DNA, we also compared bi-allelic SNPs to phased alleles (50bp RAD loci). Population structure analyses confirmed that boundaries separating species are sharp, and all clines are <65km wide. Cline center estimates were consistent between SNPs and phased alleles, but cline width estimates were significantly different with the SNPs producing wider estimates. The mitochondrial clines are narrower and shifted 4-20km southward in comparison to the nuclear clines in all three hybrid zones, indicating that either each of the species has sex-biased dispersal (males northward or females southward), the population densities are unequal, or that the hybrid zones are moving north over time. These comparisons indicate that some patterns of hybridization are similar across hybrid zones (mtDNA clines all narrower and shifted to the south), whereas cline width is variable. Hybridization in the L. fitzingerii group is common and geographically localized; further studies are needed to investigate whether hybrid zones act as hard species boundaries or promoters of speciation through processes such as reinforcement. Nonetheless, this study provides insights into both biotic and abiotic mechanisms helping to maintain species boundaries within the speciose Liolaemus system.